Respuestas

  • Usuario de Brainly
2013-06-27T01:33:25+02:00
(6-3.8):2-(-30):(-1-4) =
(6 - 24) : 2 - ( - 30): ( -5) =
( - 18) : 2 - 6 =
 - 9 - 6 =  - 15

(7+10):(-1)-(4-7).3 =
  17 : ( -1) - ( - 3).3 =
   - 17 + 9 = - 8

10+(-3).(-4) - 8 =
10 + 12 - 8 =
 22 - 8 = 14

25: (-4+9) + 3.(-3) =
25 :( 5) + ( - 9) =
  5 - 9 = - 4
 
(-10 - 5.2).2 - 6 =
 ( -10 -10).2 - 6 =
  - 20 . 2 - 6 =
   - 40 - 6 = - 46

(10+4).(-2) - (3+15) =
( 14) (-2) - (18) =
   - 28 - 18 = - 46

-25 + 5.(2-5) =
- 25 + 5 ( - 3) =
- 25 - 15 = - 40

espero que te sirva, salu2!!!!

sos una re genia gracias!!!!!!!!!!!!!!!!1
De nada!! para eso estamos ....tratamos de ayudar!! salu2!!!